Immunohistochemical detection of Ca antigen in normal, dysplastic and neoplastic squamous epithelia of the human uterine cervix. Issue 1 (January 1984) - Lloyd, J M; O'Dowd, T; Driver, M; Tee, D E
Abstract : Immunohistochemical staining was performed on biopsies and cytological samples from normal, dysplastic and neoplastic squamous epithelia using the monoclonal Ca 1 antibody. The results of staining 92 biopsies and 20 cytological samples are described and it is reported that positive staining with Ca 1 antibody was detected in normal, dysplastic and neoplastic epithelia. The role of the Ca 1 antibody in the study of cervical cancer is discussed.